Acute Disseminated Encephalomyelitis: Outcome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
The clinical and neuroimaging findings in 84 consecutive children with acute disseminated encephalomyelitis (ADEM) were studied prospectively, between March 1988 and July 2000, in relation to outcome at the National Pediatric Hospital, Buenos Aires, Argentina.